Journal of Human Sport and Exercise - 2021 - Spring Conferences of Sports Science 2021
DOI: 10.14198/jhse.2021.16.proc4.05
|View full text |Cite
|
Sign up to set email alerts
|

Pencak silat combat match: Time motion analysis in elite athletes championship

Abstract: Pencak silat is a martial art characterized by full body contact fighting. Its physical demand during official games has so far received little scientific attention. For this reason, the purpose of this study is to investigate the physical intensity based on the time structure during elite pencak silat competition. The classification of intensity in this study namely high intensity activities (HIA), low intensity activities (LIA), and off position (OP). A total of 45 fights from 3 elite competitions were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…These steps were simulated the duration of a match. It aligns with [14] that the analysis of pencak silat combat results in the fight category is characterized by irregular patterns. The average duration of combat time was 2.6 ± 0.6 s and interspersed with the preparation step of non-combat activities with an average of 8.4 ± 3.6 s. In addition, in a match situation, there is a "pause" or stoppage by the referee with an average time of 11.3 ± 1.8 s.…”
Section: Methodssupporting
confidence: 74%
“…These steps were simulated the duration of a match. It aligns with [14] that the analysis of pencak silat combat results in the fight category is characterized by irregular patterns. The average duration of combat time was 2.6 ± 0.6 s and interspersed with the preparation step of non-combat activities with an average of 8.4 ± 3.6 s. In addition, in a match situation, there is a "pause" or stoppage by the referee with an average time of 11.3 ± 1.8 s.…”
Section: Methodssupporting
confidence: 74%
“…From some of the biomotor components above, strength is an important foundation for obtaining these abilities well. For example, biomotor power is obtained from a combination of strength and speed [8].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, research on the physical demands of pencak silat competition shows that it is characterized by full-body contact combat, indicating the involvement of various parts of the body in the sport (Nurul Khotimah et al, 2022). Furthermore, the development of training models for children in pencak silat emphasizes the importance of adapting movements with biomotor components, indicating the involvement of different body elements in the training process (Subekti et al, 2021). Therefore, it can be concluded that pencak silat utilizes every element of the human body in its movements.…”
Section: Introductionmentioning
confidence: 99%